The Correlation of Environment and Smoking Habit of Family Members with Smoking Habit of School Age Children - Tri Ratnaningsih; Tri Peni; ADAM FERDIANSYAH (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The smoking habit of school-age children is a phenomenon that is easily found in various regions in Indonesia. Smoking habit in school-age children is not only uncomfortable to look at but also has the potential to trigger an increasing health problems caused by smoking habit. Some of the factors that influence smoking habit in school-age children are the environment and smoking behavior of family members. This study was using analytic research design with a cross sectional approach. The sample in this study were school-age children (grade V and grade VI) in Mangelo Village, Mojokerto Regency who met the research criteria as many as 51 respondents who were taken using a purposive sampling technique. The independent variables in this study were the environment and smoking habits of family members. The dependent variable in this study is the smoking habits of school-age children. The research instrument used in this study was a modified questionnaire using a Google form to implement health protocols during the Covid-19 pandemic. In order to determine the correlation between the environment and the smoking behavior of family members with the smoking habits of school-age children in Mangelo Village, Mojokerto Regency, the chi square test was used with a significance of α : 0.05. There was an environmental correlation to the smoking habits of school-age children in Mangelo Village, Mojokerto Regency with a sig (2-tailed) value of 0.003 <α (0.05) and there was a correlation between the smoking behavior of family members with the smoking habits of school-age children in Mangelo Village, Mojokerto Regency with sig value (2-tailed) of 0.020 <α (0.05). Parents' affection which was manifested in the form of good parenting for school-age children would provide positive support to school-age children in dealing with any negative influences such as smoking behavior.